Effects of Adulteration on Diesel Oil with Kerosene Fuel in Ghana - K.O. Boadu (Journal of Applied Sciences and Environmental Management)
This research was carried out to estimate the proportional mixtures of diesel and kerosene that easily shows the incidence of fuel adulteration. Two samples (kerosene and diesel) were obtained from a base stock at Tema Oil Refinery and the purity for both the kerosene and diesel were ensured by testing their density, kinematic viscosity, distillation and flash point. The values obtained for these parameters after the analyses carried out are density at 15°C falls within 816-850 kgm3 ; the flashpoint was found to be within 48-73°C; distillation at 360 °C were in the range of 96-98°C and kinematic viscosity at 37.8 °C were also in the range 1.5-3.5 mm2 /s. The parameters analysed are good indicators in the assessment of the extent to which diesel fuel can be adulterated by kerosene. The above parameters were analysed using both standard American Society for Testing and Materials (ASTM) methods and Statistical Package for the Social Sciences (SPSS) version 23 statistical tools. The values obtained from the experiments conform to respective standards of United States Environmental Protection Agency (USEPA) regulations at 40CFR 79, 2017 and other literature values. The correlation coefficient (R2 ) obtained after statistical analyses are 0.9984 for flash point, 0.9985 for density, 0.9405 for distillation and 0.9962 for kinematic viscosity. Also, analyses of variance (ANOVA) was Pr > F <0.0001 for all the parameters. However, the F calculated for various parameters are 669.3500 for flash point, 693.7294 for density, 16.6000 for distillation and 272.3459 for kinematic viscosity. This shows that the various parameters play a significant role in the adulteration of diesel fuel.